2009
DOI: 10.1016/j.baae.2008.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Can root-feeders alter the composition of AMF communities? Experimental evidence from the dune grass Ammophila arenaria

Abstract: Root herbivores and plant mutualists, such as arbuscular mycorrhizal fungi (AMF), have a significant effect on the structure and dynamic of plant communities. Nevertheless, the interactions between the two groups of organisms in natural ecosystems are far from understood. We carried out an inoculation experiment to examine the effect of two root herbivores, Pratylenchus penetrans and P. dunensis (Nematoda), on the composition of the AMF communities associated with two populations of the dune grass Ammophila ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Results from some other studies indicate AMF may increase plant reproduction and tillering, rather than individual tiller growth per se (Gemma and Koske, 1989;Hartnett et al, 1993;Boudreau and Houle, 2001), though seedlings have benefited from AMF in other systems (e.g., van der Heijden, 2004). Alternatively, other organisms, such as nematodes or parasitic fungi, in the whole-soil inoculum may have counteracted any benefit provided by AMF (e.g., Rodriguez-Echeverria et al, 2009). Further work comparing soil communities across dune systems is needed to provide additional insight.…”
Section: Discussionmentioning
confidence: 95%
“…Results from some other studies indicate AMF may increase plant reproduction and tillering, rather than individual tiller growth per se (Gemma and Koske, 1989;Hartnett et al, 1993;Boudreau and Houle, 2001), though seedlings have benefited from AMF in other systems (e.g., van der Heijden, 2004). Alternatively, other organisms, such as nematodes or parasitic fungi, in the whole-soil inoculum may have counteracted any benefit provided by AMF (e.g., Rodriguez-Echeverria et al, 2009). Further work comparing soil communities across dune systems is needed to provide additional insight.…”
Section: Discussionmentioning
confidence: 95%
“…3). Rodríguez-Echevarría et al (27) also found that nematodes altered the compositions of the AMF communities inside Ammophila arenaria roots, although they did not identify the AMF species. We found similar numbers of AMF sequence types in infected and uninfected roots (16 and 17, respectively); however, the compositions of the two AMF communities clearly differed, with only 12 fungal sequence types being shared.…”
Section: Discussionmentioning
confidence: 99%
“…A previous molecular study using PCR-denaturing gradient gel electrophoresis (DGGE) indicated that the presence of nematodes alters the composition of AMF communities inside Ammophila arenaria roots (27). However, when this methodology is used without subsequent cloning procedures, it is not possible to determine the identities of the AMF, since this technique is based on the observation of the composition of the fungal or bacterial communities using DGGE profiles (3).…”
mentioning
confidence: 99%
“…In a previous study, we discovered an undescribed species of class I endophyte in the genus Epichloë (Clavicipitaceae) at low frequencies in natural A. breviligulata populations of the Great Lakes, but in very high frequencies in commercial stocks often used in dune restoration efforts (Emery et al 2010). These fungi occur systemically in plants, often conferring protection against abiotic or biotic stressors such as drought, heat, herbivores, and pathogens (Rodriguez-Echeverria et al 2009). Ammophila breviligulata plants colonized by the endophyte had a 22% increase in tiller initiation compared to uncolonized plants in growth chamber and field experiments Emery and Rudgers, unpubl.…”
Section: Introductionmentioning
confidence: 99%